Development of a TaqMan PCR assay for the identification of the non-native copepod Acartia tonsa, and detection of this species in Norwegian coastal waters. (30th April 2021) - Moseid, Camilla V S; Falkenhaug, Tone; Slettan, Audun
Abstract: Molecular based assays for detection of species are a powerful tool to supplement morphological methods that may be time and labor intensive. Here we describe a sensitive TaqMan real time polymerase chain reaction assay that specifically detects the presence of Acartia tonsa in mixed plankton samples. The assay is used to find this non-native copepod in samples collected in Norwegian coastal waters.